1983
DOI: 10.1073/pnas.80.2.560
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus types 6 and 11 DNA sequences in genital and laryngeal papillomas and in some cervical cancers.

Abstract: Human genital tumors as well as recurrent laryngeal papillomas were analyzed for the presence of human papil, lomavirus (HPV)6 and HPV 11 sequences. HPV 11 DNA was found in 7 of 14 laryngeal papillomas; in the 7 other tumors no HPV DNA was demonstrated. HPV 11 DNA was also found in all five atypical condylomata of the cervix included in this study. Condylomata acuminata mainly contained HPV 6 DNA. From 63 biopsy specimens, 41 clearly harbored HPV 6 DNA and 13 harbored HPV 11 DNA. In three tumors accurate typin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
285
2
10

Year Published

1983
1983
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 767 publications
(307 citation statements)
references
References 12 publications
10
285
2
10
Order By: Relevance
“…Nonetheless, malignant transformation of lesions caused by HPV 11 does occur, although it is an infrequent occurrence (15,16). DNA sequence analysis has shown that specific viral mutations are associated with malignant transformation, demonstrating the role of specific viral genes in oncogenesis (17).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, malignant transformation of lesions caused by HPV 11 does occur, although it is an infrequent occurrence (15,16). DNA sequence analysis has shown that specific viral mutations are associated with malignant transformation, demonstrating the role of specific viral genes in oncogenesis (17).…”
Section: Discussionmentioning
confidence: 99%
“…RRP is a squamous lesion within the respiratory tract which in the majority of cases is caused by HPV6 and 11 at a prevalence rate varying between 50 and 90% (Gissmann et al, 1983;Major et al, 2005). The reported variation in prevalence rate of HPV can be attributed to differences between detection methods, sensitivity and types of samples.…”
Section: Discussionmentioning
confidence: 99%
“…These include HPV-6, HPV-11, HPV-16 and HPV-18 which have been associated with tumours of the genital tract. HPV-6 and HPV-11 DNAs have been identified in benign lesions whereas HPV-16 and HPV-18 DNAs have been found in malignant lesions (Gissmann et al, 1983;Ikenberg et al, 1983;Boshart et al, 1984;Crum et al, 1984). DNAs are also present in a number of cell lines derived from human cervical carcinomas, and in addition these DNAs are transcribed (Schwarz et al, 1985 ;Yee et al, 1985).…”
Section: Introductionmentioning
confidence: 99%